Uma Estratégia de migração dinâmica de máquinas virtuais para economia de energia em ambientes computacionais virtualizados - Magalhães, Deborah Maria Vieira (2012)
In clusters and virtualized data centers, the resources must be managed effectively by maximising the SLA fulfilment while minimising the cost. This work proposes a strategy for dynamic resource allocation in virtualized computing environments in order to reduce energy consumption without compromising performance requirements concerning availability and SLA violation. The proposed algorithms, based on classical heuristics, perform virtual machines migration between distinct hosts according to the variation in resources demand. These algorithms were evaluated from measurements in a real environment composed by heterogeneous virtualized hosts. We evaluate their performance in four different scenarios based on the CPU and memory utilization, number of migrations and energy consumption. In general, the results show that the algorithms responsible for consolidation and distribution of virtual machines between hosts are able to reduce energy consumption and dissipate the idle and overload points.